Analysis of Self and Retrieval Generated Priming in Human Recognition Memory - Nitka, Aleksander Wojciech (2021)
In this report, I have documented the development of an eye-tracking procedure able to distinguish between the influence of Self (SGP) and Retrieval Generated Priming (RGP), effects postulated by the Wagner’s Sometimes Opponent Process (SOP) model. The procedures of Relative Recency (RR), Object in Place (OIP) and Object in Context (OIC) map onto the two postulated mechanisms and so the primary goal was to exhibit both effects in the human eye-tracking procedure. In the RR procedure, participants have demonstrated to look at stimuli which were pre- exposed earlier in the past when compared with a more recently presented one. In both OIP and OIC, participants engaged more with stimuli which were presented in either a novel spatial arrangement or accompanied by a novel context. Such effects mirror the SOP-derived predictions and demonstrate the involvement of SGP and RGP in the human recognition memory. A key difference between the SGP- and RGP-enabled effects is the influence of time. Hence, the model is evaluated regarding such manipulations applied to RR, OIC and OIP procedures. To that extent, the mathematical tenets of SOP were employed to simulate the experimental procedures, whose predicted results were experimentally tested. Overall, both mechanisms were demonstrated, however, their effects were sensitive to a time-dependent decay. Overall, the experiments reported yield support for the associative account of recognition memory. I argue that the SOP offers a parsimonious, computational, and robust model of recognition memory and that the procedures developed for this thesis offer a more sensitive measure than the procedures currently used for that purpose.